Pengaruh Perceived Organizational Support dan Affective Commitment Terhadap Produktivitas Kerja Pada Karyawan Bagian Produksi PT. Semen Padang - Syahril Syahril; Nofri Yendra (Universitas Dharma Andalas, 2022)
The variables of this research are Perceived Organizational Support (X1), Affective Organizational (X2) and Work Productivity variable (Y.). Perception of organizational support is a variable that can affect the increase in work productivity, as well as the Affective Commitment variable in the organization can also have an influence on work productivity of employees who work at PT. Semen Padang Production Department.. The data analysis method used in this research is multiple linear regression analysis method with the sampling technique using purposive sampling technique with a total sample of 100 from a population of 144 people. The results of this study indicate that the perceived organizational support variable has a significant effect on work productivity for employees of PT. Semen Padang production division. Likewise, the variable affective commitment (X2) also has a significant effect on work productivity at PT. Semen Padang Production Department. Furthermore, the two variables, namely perceived organizational support and affective commitment, simultaneously have a significant effect on work productivity at PT. Semen Padang production department Abstrak The variables of this research are Perceived Organizational Support (X1), Affective Organizational (X2) and Work Productivity variable (Y.). Perception of organizational support is a variable that can affect the increase in work productivity, as well as the Affective Commitment variable in the organization can also have an influence on work productivity of employees who work at PT. Semen Padang Production Department.. The data analysis method used in this research is multiple linear regression analysis method with the sampling technique using purposive sampling technique with a total sample of 100 from a population of 144 people. The results of this study indicate that the perceived organizational support variable has a significant effect on work productivity for employees of PT. Semen Padang production division. Likewise, the variable affective commitment (X2) also has a significant effect on work productivity at PT. Semen Padang Production Department. Furthermore, the two variables, namely perceived organizational support and affective commitment, simultaneously have a significant effect on work productivity at PT. Semen Padang production department